Transient Glaucoma After An Epidural Steroid Injection: A Case Report - Islam, Md Ashraful; Das, Polak Kumar; Islam, Md Rafiqul; Milon, Md Hafizur Rahman; Khan, Md Asmaul Hossain (KYAMC Journal, 2017)
Background: Steroids are recognized as a beneficial treatment for various medical conditions, yet clinically relevant side effects of steroids are common and problematic, ranging from a minor case of acne to a potentially life-threatening Addisonian crisis. In anesthetic medicine, the use of epidural steroid injections (ESIs) for chronic low back pain and other radicular pain-related conditions has become standard practice in interventional pain management. Case Report: We report the case of a patient who experienced sudden bilateral blurred vision after receiving an ESI and required urgent ophthalmic interventions and follow-up care. The main clinical findings from this case showed that the patient had high intraocular pressure (IOP) that caused unexpected short-term vision loss. The symptom resolved after 4 months without ophthalmic treatment. Conclusion: Clinicians should inform patients about the possibility of visual complications associated with pain procedures involving steroids. Among the high-risk groups with predisposing factors, such as uncontrolled hypertension and diabetes mellitus, routine eye tests that include measuring IOP prior to ESI should be recommended as a preventive measure. Alternative pain management therapies should be considered if possible. Comprehensive planning of patient care will also ensure safety and prevent unwanted outcomes, particularly with high-risk patients receiving steroids for pain procedures. KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 821-824